Exogenous spatial attention is functional in paralytic strabismics - Willeford, Kevin T.; McPeek, Robert M. (Frontiers in Neuroscience, 2025)
IntroductionThe absence of exogenous cueing effects in patients with paralytic strabismus has been cited as evidence for an obligate linkage between movement execution and attentional allocation.MethodsThe present study challenges this interpretation through two experiments that measured the impact of visual cues, intended to facilitate or inhibit shifts of spatial attention, on the latencies of target-directed responses. By including a no-cue control condition, we assessed both the presence and direction of cue-induced attentional modulation.ResultsOur results show that all patients’ patterns of saccadic (Experiment I) and keypress (Experiment II) response latencies showed classic signatures of cue-target interactions: movements initiated in response to targets spatially proximate to cues were initiated fastest whereas movements initiated toward targets spatially distal from cues were initiated slowest. This trend held true when grouping latencies by cue-saccade offset to account for small errors in saccade landing position in Experiment I. Though the patients’ data exhibited small degrees of idiosyncrasy, most patients’ mean normalized latencies also fell within the range of latencies observed in non-strabismic participants.DiscussionThese findings support the notion that premotor structures may program attentional shifts in an effector-independent manner and motivate future investigations to explore how, not if, exogenous spatial attention is deployed in paralytic strabismics.